Consulting Higher Education in Africa: A Strategic Case Study - Brice, David; Katzenstein, James; Norman, Thomas J. (Senate Hall, 2019)
As part of a research project grant from the Mervin M. Dymally African-American Political and Economic Institute, this paper is a case study of US College (USC), a new entrepreneurial private college in Ethiopia, and its developing relationship with California State University Dominguez Hills (CSUDH). USC is struggling to create sustainability in an underdeveloped but rapidly growing economy and CSUDH is assisting it in incorporating world-class curriculum and standards. The challenges of developing an entrepreneurial twinning relationship between the two universities, to the mutual benefit of both, are explored. How will CSUDH faculty help a struggling Ethiopian college entrepreneurially develop the ability to deliver a first-world level of education; in a reciprocal relationship that also enhances CSUDH?
Keywords: Africa|entrepreneurship|business education|developing economy|educational entrepreneurship|transferring capability